Chronic constipation and abdominal pain: Independent or closely interrelated symptoms?. Issue 8 (21st January 2020) - Wong, May Y W; Hebbard, Geoffrey; Gibson, Peter R; Burgell, Rebecca E
Abstract: Constipation is both a symptom and a disorder, seen in both functional constipation and irritable bowel syndrome with constipation predominance (IBS‐C). Despite the Rome IV criteria distinguishing between these conditions, they share many therapeutic approaches. This review aims to explore the relationship between constipation and abdominal pain and assess the evidence surrounding whether laxation improves abdominal pain and whether such a response to laxation differs between IBS‐C and functional constipation. In patients with functional constipation, increasing frequency of bowel motions by laxatives regardless of mechanism of action is associated with reductions in the severity of abdominal pain, supporting the role of constipation as a contributor to abdominal discomfort. In patients with IBS‐C, evidence from systematic reviews indicates that abdominal pain is driven by factors additional to constipation alone and that visceral analgesic modulation is also needed to optimize pain. Changing definitions of IBS‐C and heterogeneity in clinical trial design including endpoints have raised uncertainty about the comparative ability of older laxatives without known neuromodulatory effects to improve chronic abdominal pain compared with new secretagogues and prokinetics for the management of IBS‐C. While it is known that abdominal pain is associated with constipation and laxation contributes to relief of that pain, it remains unproven whether proposed visceral analgesic properties of new laxatives provide greater pain relief than laxation alone. However, it is likely that the response to laxation in IBS‐C is only part of the puzzle.